Diagnostic accuracy of tru-cut biopsy of breast lumps at University College Hospital, Ibadan (2015)
Background: Tru-cut needle biopsies form an integral part of Triple assessment of breast cancer and include clinical assessment, mammography and core needle biopsy. No study has been done to evaluate the validity of the procedure in our environment. This study was done to evaluate the validity of core needle biopsies in our centre. Method: A retrospective study of patients with tru-cut needle biopsies of breast lumps and follow-up excisional biopsy or mastectomy done in the Department of Surgery, University College Hospital, Ibadan over a ten year period was done. Fifty one patients who fulfilled the inclusion criteria had their records obtained from the Department of Pathology. The diagnosis was classified into benign and malignant with the excisional biopsy or mastectomy diagnosis used as the gold standard. The sensitivity, specificity and accuracy were calculated and kappa was also done to evaluate the degree of agreement. Results: A total of 51 cases were included in this study. The average age of the patients was 47 ± 13 years with a range from 19 to 81 years. Thirty of the biopsies (59%) had a definitive diagnosis of malignancy while twenty one (41%) were benign. The overall sensitivity, specificity and accuracy were 86%, 71% and 80.4% respectively. The specificity of malignant biopsies was 68% while benign was 35%. The level of agreement for malignant biopsies was higher than benign biopsies with a kappa of 0.39 for malignant diagnosis as against 0.29 for benign. Conclusion: Tru-cut needle biopsies have a comparable sensitivity and specificity to excisional biopsies. Diagnostic accuracy can be further enhanced with the adoption of image guided biopsies.